Novel visual detection technique of isothermal Ligation-dependent probe combined with hybridization chain reaction and hydrogel for the wild edible mushroom component - Nali Zhou; Hanyue Zhang; Shuna Xiang; Yingting Lin; Ying Shang (Applied Food Research)
Multiplex ligation-dependent probe amplification (MLPA) is a high-throughput detection technology with superior specificity and sensitivity, which combines ligation-dependent probe hybridization and PCR amplification. However, the whole process requires repeated temperature change, and the detection results need high resolution agarose electrophoresis or capillary electrophoresis, which limits its application. In viewing of its advantages, an isothermal reaction process based on that combined Hybridization chain reaction (HCR) and hydrogel technology is developed, in order to achieve visual output of detection results without relying on any large instruments and equipment. The edible mushroom is taken as the detection target, and the LP probes were designed according to its reported endogenous reference gene. Through optimizing the reaction conditions, only the samples contained target component, the result showed irregular hydrogel. This visual detection system had good specificity, which detection limit was as low as 0.32 ng/μL. The development of this method provides a new strategy for species identification and adulteration detection of edible mushroom, even for more DNA target detection.